Uniwersytet Wileński i wizytacja generalna szkół jemu podległych w 1803 roku - Prašmantaitė, Aldona (Biuletyn Historii Wychowania, 2023)
The article shows the course of the general visitation of schools of the Vilnius School District [WOS] in 1803. It was the first year when Vilnius Visegrána University, transformed into the Imperial University of Vilnius as a tertiary education institution, took over the helm and control of lower-level schools in the designated territorial area, namely the school district. In the legal acts of the Russian Empire, regulating the activities of the reformed Vilnius University, the sanctioned principle of the continuation of the Commission of National Education tradition was manifested in practice during the visitation of the WOS schools in 1803. The article presents the origin of general visitations in the history of the University and the instructions addressed to the visitators. Literature on the subject and the sources made it possible to show the visitators and to present their collective portrait.